Implementasi Metode Marker Based Tracking Augmented Reality Untuk Pengenalan Format Penulisan Skenario Film Berbasis Android - Ryan Gesvary; Achmad Udin Zailani (CV. Multi Kreasi Media, 2024)
The introduction of this film script writing format aims to introduce AR augmented reality to students at Teruna Integrated Vocational School, Borces 1, majoring in broadcasting. The low intention to learn is influenced by learning media such as Power Point presentation texts, which are displayed via projectors, student web portals and practicums. Based on the results of the questionnaire given to students, the media used was felt to be less interesting, and this influenced the students' lack of understanding of the material presented by the teacher. To overcome this, more interactive learning media is needed, utilizing augmented reality technology. The method for building system development applications uses the Multimedia Development Cycle (MDLC), while the application creation method uses marker based tracking. Place the marker on two cubes that will be directed at the camera to produce objects, namely: EXT, INT, Character, Actionlines, Dialogue. By applying augmented reality technology to the application for introducing film screenplay writing formats, there are also advantages, namely that we can display film screenplay writing formats in 3D and add information regarding the introduction of screenwriting formats. This makes it easier for students in the learning process to introduce the film screenplay writing format.